Soil biodiversity and ecological intensification for sustainable agriculture - Erktan, Amandine; Blanchart, Eric; Pulleman, Mirjam; Trap, Jean (Springer, 2024)
Soil biodiversity is pivotal for ecological intensification of agriculture by enhancing soil functions, sustainable crop production and resilience to environmental shocks and disturbances. However, a detailed understanding of mechanisms in field conditions to inform ecological intensification strategies based on the beneficial effects of soil biodiversity on soil functions remains to be established. This special issue gathers thirteen original studies investigating the influence of soil biodiversity (bacteria, fungi, nematodes, collembolans, earthworms, and plant roots) on soil functions, namely soil C transformation and nutrient cycling, soil structure maintenance, biological pest regulation, water regulation and metal contaminant mitigation. Whether in field or microcosms conditions, most articles in this special issue focus on how agroecological practices impact the nexus between soil biodiversity-soil functioning and sustainable crop production (soil/crop management). The issue notably covers the effect of varietal selection and their diversity, crop diversification in time and in space, reduced tillage, and organic residue management over short (few weeks) and long-term (> 10 years) periods. Key insights revealed that the abundance of specific species/groups was the main driver of soil functions, while organism diversity influenced soil multifunctionality. Main research gaps highlighted include limited consideration of temporal variations (long or short term), the links between soil water regulation and soil biodiversity, better consideration of trophic interactions, and the need to define a common approach to measure and model the concomitant effects of soil biodiversity on multiple soil functions in partnership with farmers.